Cryogenic carbon dioxide separation from natural gas: A review based on conventional and novel emerging technologies - Maqsood, K. (Walter de Gruyter GmbH, 2014)
Fossil fuels are the major contributors to the emission of anthropogenic carbon dioxide (CO2) to the atmosphere, rendering global warming a challenging issue to the researchers and industries. Although natural gas has been recommended as a clean fuel compared to other fossil fuels, geological sources of natural gas are not free of impurities. Economical commercialization of natural gas with high sour gas contents as well as facilitating the geosequestration of sour gases for enhanced oil recovery (EOR) need several environmentally sound and cost-effective gas separation methods. Moreover, stringent restrictions should be drawn to mitigate the unfettered greenhouse gas emissions to the atmosphere. In the present study, existing low-temperature conventional CO2 capture methods, namely, cryogenic distillation process along with emerging nonconventional and hybrid methods, have been demonstrated. Also, the limitations and operational conditions during the application of these processes have been mentioned. The future prospects of the emerging technologies have been compared with conventional methods. Hybrid cryogenic distillation networks for multiproduct industrial production of different hydrocarbons and CO2 products at higher pressures of 40 bar and above showed promising potentials. A concise classification and summary of innovative emerging technologies along with conventional methods has been presented in this paper for possible future commercial exploitation.